2019
DOI: 10.1177/2393957518815288
|View full text |Cite
|
Sign up to set email alerts
|

Lean Intrapreneurship for Networked Manufacturing Enterprises

Abstract: Manufacturing processes are usually imbedded in cross-company value and supply chains. Most manufacturing companies are currently encountering the obligation to react on their rapidly changing network environments. For companies, which are willing to remain competitive and to keep their position in the global business environment, continuous improvement and innovation of production system processes has become a necessity. Lean manufacturing and lean thinking represent meanwhile traditional frameworks for impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(29 reference statements)
0
4
1
Order By: Relevance
“…This also supports Hsieh and Wu (2019), who have highlighted information systems as sources of intrapreneurship. Finally, the results on model invariance based on business type do not clarify the differences between industries and services that previous studies have suggested (Atari & Prause, 2019;Lages et al, 2017).…”
Section: Discussion and Theoretical Implicationscontrasting
confidence: 91%
See 1 more Smart Citation
“…This also supports Hsieh and Wu (2019), who have highlighted information systems as sources of intrapreneurship. Finally, the results on model invariance based on business type do not clarify the differences between industries and services that previous studies have suggested (Atari & Prause, 2019;Lages et al, 2017).…”
Section: Discussion and Theoretical Implicationscontrasting
confidence: 91%
“…For instance, industries and manufacturers are normally involved in value chains and production systems. For industries that wish to remain competitive, continuous improvements and innovations in production processes have become imperative (Atari & Prause, 2019). On the other hand, in a service company, the focus is tending towards relying less on innovation and more on the intrinsic behaviour of intrapreneurs, by way of proactiveness and risk-taking (Lages et al, 2017).…”
Section: Moderator Role Of the Business Contextmentioning
confidence: 99%
“…This leads us to further explore for more evidence of efficiency as a positive result of projects, following in particular the effects of members of the team on project outcomes, already evidenced in the existing literature (Juras, 2019;Tam et al, 2020). We propose that intrapreneurial individuals conduct project activities more efficiently to reach a far better result for the company and the project, based on innovation principles of the intrapreneur (Atari & Prause, 2019). H2: Intrapreneurial behavior will positively influence efficiency.…”
Section: Intrapreneurial Behavior Influences Project Success Dimensionsmentioning
confidence: 91%
“…Kaizen, Lean, LSS and Agile (Atari and Prause, 2019;Berhe, 2022;Chow and Cao, 2008;Kinder and Burgoyne, 2013;Kuiper et al, 2022;Swarnakar et al, 2020) Inadequate level of documentation Agile (Chow and Cao, 2008;Maiden and Jones, 2023) Source: Authors' own work…”
Section: Supply Chain Disruptionmentioning
confidence: 99%